2018
DOI: 10.2174/1874285801812010181
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Actinobacterial Communities from Arauca River Sediments (Colombia) Reveals Antimicrobial Potential Presented in Low Abundant Isolates

Abstract: Introduction:New strategies have been arisen to set a rapid and effective screening for selection of microorganism with bioactive potential. This study suggests that combination of physicochemical pretreatments and taxonomic dereplication of microbial collections through MALDI-TOF MS, facilitates the detection of low abundance actinobacteria with potential as a source of antimicrobial agents.Material and Methods:An unstudied microbial community from a tropical river sediment in Colombian Orinoquía is described… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 58 publications
(63 reference statements)
0
12
0
Order By: Relevance
“…They present pigmentation depending on the medium in which they are inoculated, which has been seen in other studies [43]. Each strain of Streptomyces presented above was identified by sequencing the 16S gene in a parallel study [38] and as previously reported, all strains showed an identity greater than 98.7% [44]. The strain 5 was identified as Streptomyces lunalinharesii, the strain 67 as Streptomyces puniciscabiei, the strain 112 as Streptomyces lacticiproducens, the strain 126 as Streptomyces phaeogriseichromatogenes, the strain 220 as Streptomyces phaeoluteigriseus, the strain 276 as Streptomyces griseofuscus and the strain 326 as Streptomyces mashuensis (Table S3).…”
Section: Morphological Identificationmentioning
confidence: 75%
See 4 more Smart Citations
“…They present pigmentation depending on the medium in which they are inoculated, which has been seen in other studies [43]. Each strain of Streptomyces presented above was identified by sequencing the 16S gene in a parallel study [38] and as previously reported, all strains showed an identity greater than 98.7% [44]. The strain 5 was identified as Streptomyces lunalinharesii, the strain 67 as Streptomyces puniciscabiei, the strain 112 as Streptomyces lacticiproducens, the strain 126 as Streptomyces phaeogriseichromatogenes, the strain 220 as Streptomyces phaeoluteigriseus, the strain 276 as Streptomyces griseofuscus and the strain 326 as Streptomyces mashuensis (Table S3).…”
Section: Morphological Identificationmentioning
confidence: 75%
“…Due to that, an analysis to determine an L-asparaginase production was performed on all these strains. According to other studies, high production of secondary metabolites could lead to better production of enzymes [38]. Therefore, from these results, 25 strains were highlighted due to high L-asparaginase/Lglutaminase activity presenting the production of the ammonium cation by the enzymatic action, which was determined by the color changing of phenol red indicator in the medium.…”
Section: Selection Of L-asparaginase and L-glutaminase Producing Strainsmentioning
confidence: 89%
See 3 more Smart Citations